The grammar book : - Celce-Murcia, Marianne. (Heinle & Heinle, 1999)
In this highly acclaimed revision, grammatical descriptions and teaching suggestions are organized into sections dealing with Form, Meaning, and Use. The Grammar Book, 2/e helps teachers and future teachers grasp the linguistic system and details of English grammar, providing more information on how structures are used at the discourse level.